The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/v12040473
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Bovine Antibodies: Highly Effective New Tools against Evasive Pathogens?

Abstract: Potent antibody-mediated neutralization is critical for an organism to combat the vast array of pathogens it will face during its lifetime. Due to the potential genetic diversity of some viruses, such as HIV-1 and influenza, standard neutralizing antibodies are often ineffective or easily evaded as their targets are masked or rapidly mutated. This has thwarted efforts to both prevent and treat HIV-1 infections and means that entirely new formulations are required to vaccinate against influenza each year. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…BrNAbs with long CDR H3 are promising candidates for prophylaxis and antibody‐based immunotherapy 122,123 . Other viruses, such as influenza or SARS‐CoV‐2, 124 may benefit from a similar approach, eliminating the need for expensive annual vaccinations or offering a therapeutic response to prevent pandemic outbreaks 125 . The TcB platform for producing hIgs is still relatively new, and products are only now making their way into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BrNAbs with long CDR H3 are promising candidates for prophylaxis and antibody‐based immunotherapy 122,123 . Other viruses, such as influenza or SARS‐CoV‐2, 124 may benefit from a similar approach, eliminating the need for expensive annual vaccinations or offering a therapeutic response to prevent pandemic outbreaks 125 . The TcB platform for producing hIgs is still relatively new, and products are only now making their way into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…122,123 Other viruses, such as influenza or SARS-CoV-2, 124 may benefit from a similar approach, eliminating the need for expensive annual vaccinations or offering a therapeutic response to prevent pandemic outbreaks. 125 The TcB platform for producing hIgs is still relatively…”
Section: Discussionmentioning
confidence: 99%
“…The structure of bovine ultralong antibodies makes them exceptionally well suited to achieve broad and potent neutralisation [24][25][26]. This subset of Abs possesses a long CDRH3 of 40-71 amino acids (aa) which forms an extended β-strand stalk supporting a disulphide-bonded 'knob' domain [25,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, early experiments showed that ultralong CDRH3 antibodies against bovine viral diarrhoea virus (BVDV) completely lost their ability to bind BVDV once the knob domain was removed. In this regard, we may infer that ultralong CDRH3s could bind to or recognize antigen epitopes independently and therefore have great potential applications [36][37][38]. Very recently, special knob domain antibodies with an approximately 4.2 kDa of molecular weight, even smaller than nanobodies, have been reported to be derived from ultralong bovine CDRH3 [39].…”
Section: Introductionmentioning
confidence: 99%